Combinatory approach for developing silk fibroin scaffolds for cartilage regeneration - Ribeiro, V. P. (2018)
Several processing technologies and engineering strategies have been combined to create scaffolds with superior performance for efficient tissue regeneration. Cartilage tissue is a good example of that, presenting limited self-healing capacity together with a high elasticity and load-bearing properties. In this work, novel porous silk fibroin (SF) scaffolds derived from horseradish peroxidase (HRP)-mediated crosslinking of highly concentrated aqueous SF solution (16 wt.%) in combination with salt-leaching and freeze-drying methodologies were developed for articular cartilage tissue engineering (TE) applications. The HRP-crosslinked SF scaffolds presented high porosity (89.3 ± 0.6%), wide pore distribution and high interconnectivity (95.9 ± 0.8%). Moreover, a large swelling capacity and favorable degradation rate were observed up to 30 days, maintaining the porous-like structure and β-sheet conformational integrity obtained with salt-leaching and freeze-drying processing. The in vitro studies supported human adipose-derived stem cells (hASCs) adhesion, proliferation, and high glycosaminoglycans (GAGs) synthesis under chondrogenic culture conditions. Furthermore, the chondrogenic differentiation of hASCs was assessed by the expression of chondrogenic-related markers (collagen type II, Sox-9 and Aggrecan) and deposition of cartilage-specific extracellular matrix for up to 28 days. The cartilage engineered constructs also presented structural integrity as their mechanical properties were improved after chondrogenic culturing. Subcutaneous implantation of the scaffolds in CD-1 mice demonstrated no necrosis or calcification, and deeply tissue ingrowth. Collectively, the structural properties and biological performance of these porous HRP-crosslinked SF scaffolds make them promising candidates for cartilage regeneration.